Pengaruh Pemberian Ekstrak Kulit Manggis (Garcinia mangostana, Linn.) dalam Mencegah Peningkatan Kadar Kreatinin Darah pada Tikus (Rattus norvegicus) yang Diinduksi Gentamisin - Surya Adhi Prakoso; Endang Sri Hardjanti; Nur Hafidha Hikmayani (Nexus Biomedika, 2014)
Background: Gentamicin may cause nephrotoxicity and inhibits blood creatinine excretion. Xanthone from mangosteen pericarp has antioxidant and antiinflammation effects and can potentially protect kidney from inflammatory-mediated gentamicins nephrotoxicity. Gentamicin-induced renal damage can be identified from the elevation of blood creatinine levels. The purpose of this research was to find the potential of mangosteen pericarp extract to prevent the elevation of blood creatinine levels. Methods: This was an experimental research with pre and posttest controlled group design. Samples were 30 male Wistar-strain rats, 2-3 months old with approximately 200 gram of weight. Samples were randomly divided into 3 groups:control group (KN) administered Na CMC 0.5% orally, negative control group (K-) administered gentamicin 100 mg/kgBW intraperitoneally, and treatment group (KD) administered gentamicin 100 mg/kgBW intraperitoneally and 125 mg/kgBW mangosteen pericarp extract orally. Blood creatinine levels were assessed before treatment and 10 days after treatment by spectrophotometer. Data collected were analysed by Kruskal-Wallis and Mann-Whitney tests. Results: There was significant difference of blood creatinine levels before and after treatment among the three groups (p<0.001). Mann-Whitney tests showed statistically significant differences of creatinine level between KN-K- and KD-K- (p<0.001). No significant difference of blood creatinine levels was found for KN-KD comparison(p=0.06). Conclusion: Mangosteen pericarp extract at dose of 125 mg/kgBW prevented the elevation of blood creatinine levels in Wistar rats induced by gentamicin. Keywords: mangosteen pericarp extract, gentamicin, blood creatinine level